The State of Public Finances : A Cross-Country Fiscal Monitor - Mauro, Paolo (IMF Staff Position Notes; Staff Position Note, 2009)
This paper presents sharp increase in government debt has complicated the management of preexisting challenges from population aging, especially in advanced economies. The increase in debt ratios projected for these economies is the largest since World War II. The increase in deficits and debt raises complicated tradeoffs. Policymakers will need to balance two competing risks: on the one hand, a too hasty withdrawal of fiscal stimulus would risk nipping a recovery in the bud; on the other hand, with a delayed withdrawal investor concerns about sustainability may increase, leading to higher interest rates on government paper, undermining the recovery and increasing risks of a snowballing of debt. Regardless of the timing of adjustment, its necessary scale will be quite large, particularly for high-debt advanced economies. Preserving investor confidence in government solvency is key to avoiding an increase in interest rates, thereby not only preventing snowballing debt dynamics, but also ensuring that the fiscal stimulus is effective.